Confirmation of Symptomatic Tuberculosis Using Gene Xpert (MTB/RIF) among Patients within Zuru Emirate Council, Kebbi State, Nigeria - Abdulkadir B.; Ibrahim M.A. (UMYU Journal of Microbiology Research)
Tuberculosis (TB) is a bacterial infectious disease which is caused by Mycobacterium tuberculosis (MTB) and is spread from person to person via airborne droplets. It is among the